Entrepreneurship Extracurriculars in Developing Entrepreneurial Character for Elementary School Students - Moh Suryo Hardiyat; Djalal Fuadi; Laili Etika R; Minsih; Choiriyah Widyasari (International Journal of Elementary Education, 2023)
A busy schedule of lessons makes entrepreneurship learning almost impossible. On the other hand, the importance of entrepreneurial character education must be developed since children learn at the elementary school level. Entrepreneurial extracurricular activities can be one of the entrepreneurial character-building programs. The purpose of this study was to analyze the entrepreneurial character of students in the implementation of extracurricular entrepreneurship. The subjects in this study were students of grades 4 and 5 in elementary schools. This study uses a qualitative research approach with a descriptive type. The data collection techniques used include interviews and observation. The data analysis techniques use interactive models, namely data collection, data reduction, data presentation, and concluding. The data validity test was carried out using technical triangulation and source triangulation. The results showed that the implementation of entrepreneurship extracurricular activities included making crafts from used goods and making spinach chips. Entrepreneurial character instilled from making crafts from used goods and making spinach chips, namely self-confidence, hard work, self-consistency, and creative personality.  The conclusion of the research is with the implementation of entrepreneurship extracurriculars in schools, it can instill the entrepreneurial character of students needed so that later they will have an entrepreneurial attitude.